The Influence of Interaction and Entertainment Gratification through Ronal Surapradja's Image Perception on the Intention to Vote for West Java Students in the 2024 Regional Elections - Simanjuntak, Clesia Sari Mastiur; Wibowo, Kunto Adi; Fuady, Ikhsan (PERSPEKTIF, 2025)
This article examines the influence of entertainment and interaction through the perception of candidate image on the intention to choose students in West Java in the 2024 Regional Elections, with Ronal Surapradja as the research subject. This research focuses on evaluating social media's effectiveness as an effective campaign strategy in shaping voting intentions, especially in building a candidate's image. This study uses the theory of uses and gratifications with a quantitative approach. Data was collected through a questionnaire, distributed to West Java students, and then analyzed using the PLS-SEM method. The study's results showed that entertainment did not significantly affect the intention to choose Ronal Surapradja, while interaction had a significant negative influence. In addition, the perception of Ronal Surapradja's image was proven to mediate the impact of entertainment on the intention to choose. Still, it did not mediate the effect of interaction on the intention to choose. These findings show the importance of the right communication strategy in building a candidate's image on social media. Thus, it is essential to know the sound management of candidate image and the implementation of effective digital communication strategies to increase connectivity with voters, especially Generation Z, who are active on social media.